2012
DOI: 10.1080/00223891.2011.645931
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Italian Version of the Oxford Happiness Inventory in Adolescence

Abstract: An Italian adaptation of the Oxford Happiness Inventory was administered to 782 adolescents. Exploratory structural equation modeling (ESEM) was used to examine the first- and second-order factorial structure of the scale and its invariance across gender; internal consistency and construct validity were also investigated. ESEM underlined a 5-factor structure (mastery and self-fulfillment, satisfaction with life, vigor, social interest, and social cheerfulness) that measures positive psychological functioning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 81 publications
1
41
1
Order By: Relevance
“…The estimation of hierarchical ESEM models needs to rely on suboptimal two-step procedures where correlations among the first-order factors are used to estimate the higher order factor. This leads to higher order factors that are a simple reexpression (an equivalent model) of the first-order correlations (for recent illustrations, see Meleddu, Guicciardi, Scalas, & Fadda, 2012;Reise, 2012). Similarly, the estimation of bifactor models has typically been limited to CFA.…”
Section: An Integrated Test Of Multidimensionalitymentioning
confidence: 97%
“…The estimation of hierarchical ESEM models needs to rely on suboptimal two-step procedures where correlations among the first-order factors are used to estimate the higher order factor. This leads to higher order factors that are a simple reexpression (an equivalent model) of the first-order correlations (for recent illustrations, see Meleddu, Guicciardi, Scalas, & Fadda, 2012;Reise, 2012). Similarly, the estimation of bifactor models has typically been limited to CFA.…”
Section: An Integrated Test Of Multidimensionalitymentioning
confidence: 97%
“…Previous studies have often been limited to the use of a PPF total score (e.g., Furnham & Cheng, 2000), which has been suggested to be an oversimplification of the PPF construct (Meleddu et al, 2012). Specifically, this study is aimed at a better qualification of personal (extraversion and neuroticism) and environmental (perceptions of maternal/paternal care and overprotection and quality of peer relationships) factors as determinants of PPF in adolescence through the mediation of self-esteem.…”
Section: Present Studymentioning
confidence: 99%
“…In one study (Studerus et al, 2010) both CFA and ESEM showed poor fit. In three studies (Kritjansson et al, 2011;Mattsson, 2012;Meleddu et al, 2012), the CFA solution showed poor fit, whereas the ESEM showed good model fit. In five studies, the CFA models displayed poor fit and adequacy of the ESEM solutions would be dependent on the particular index focused on (Furnham et al, 2013;Marsh et al, 2009;Marsh et al, 2010;Perry et al, 2012;Rosellini & Brown, 2011).…”
Section: Introductionmentioning
confidence: 99%